Assessment of past and present soil conservation initiatives in Nigeria - Junge, B.; Deji , O.; Abaidoo, Robert C.; Chikoye, David; Stahr, Karl (2008)
In Nigeria, soil degradation has been one of t he most critical environmental problems for a long time. Hence, there has been and still is an urgent need t o develop effective soil resource management system s that can reverse the trend and sustain soil product ivity to enhance food security and alleviate povert y. An extensive literature search that started in 2006 ha s shown that soil conservation has a long tradition and earlier and present initiatives have resulted in va rious so-called on-farm and off-farm technologies. Indigenous techniques focused on soil and water con servation by ridging, mulching, constructing earth bunds and terraces, multiple cropping, fallowing, a nd the planting of trees. In colonial times, large- scale projects on soil loss control were started by the B ritish Government but many failed, as the imported technologies had little relevance in the tropics. A fter independence, more emphasis was put on soil fertility issues. Decreasing funds at the end of th e oil boom in the 1980s also restricted soil conser vation schemes. The review also revealed that most of the projects on soil conservation were carried out on research farms and only a few on-farm with the part icipation of farmers. As these have rarely been evaluated to establish ad option rates, an assessment study was performed in 2007 to analyze the effectiveness and adoption of p ast and present soil conservation initiatives, incl uding the sociological, technological, and economic aspec ts. Villages with different types of conservation technologies were visited and farmers in southwest Nigeria were interviewed to obtain information on t heir experiences. Mulching, cover cropping, and contour tillage are likely to be effective on-farm soil conservation measures practiced in Nigeria. They ar e generally adopted by farmers as they are compatible with the existing farming system, cheap and easy to install and to maintain. Agroforestry i s not popular and cut-off drainage is often rejected as i t is culturally incompatible. Education, knowledge on soil conservation, labor availability, and membership in organizations have a positive influence on the adoption rate of technologies.